2016
DOI: 10.1371/journal.pone.0165645
|View full text |Cite
|
Sign up to set email alerts
|

Increased Early Processing of Task-Irrelevant Auditory Stimuli in Older Adults

Abstract: The inhibitory deficit hypothesis of cognitive aging posits that older adults’ inability to adequately suppress processing of irrelevant information is a major source of cognitive decline. Prior research has demonstrated that in response to task-irrelevant auditory stimuli there is an age-associated increase in the amplitude of the N1 wave, an ERP marker of early perceptual processing. Here, we tested predictions derived from the inhibitory deficit hypothesis that the age-related increase in N1 would be 1) obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 87 publications
4
10
2
Order By: Relevance
“…In contrast, we found that older adults had increased N1 responses to both repeated sounds and rare high-intensity sounds. Similarly, one previous study found an age-related increase in N1 amplitude for both repeated sounds and novel sounds (Tusch et al, 2016). The authors suggest that the increase in these responses could reflect an adaptive response to compensate for reduced processing speed in older adults.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In contrast, we found that older adults had increased N1 responses to both repeated sounds and rare high-intensity sounds. Similarly, one previous study found an age-related increase in N1 amplitude for both repeated sounds and novel sounds (Tusch et al, 2016). The authors suggest that the increase in these responses could reflect an adaptive response to compensate for reduced processing speed in older adults.…”
Section: Discussionsupporting
confidence: 67%
“…For N1 sensory gating, responses to both standard and deviant sounds (see also Anderer et al, 1998;Tusch et al, 2016;Strömmer et al, 2017) for the conditions (increment and decrement) were included. For standard sounds, only responses to pre-deviant standards were included in the analysis because they had been repeated at least twice and therefore enabled an examination of the neural suppression related to stimulus repetition.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of primary task load on the P3a to novel auditory events also is uncertain. Our work (Simon et al, 2016 ; Tusch et al, 2016a ) and that of others (SanMiguel et al, 2010a ; Sörqvist and Marsh, 2015 ; Sörqvist et al, 2016 ) lead to the prediction that higher primary task difficulty protects against distraction by increasing focal-task engagement, which would result in a smaller novelty P3a under the high load for both age groups. Finding such a result would pose a challenge to the load theory of attention (Lavie et al, 2004 ; Lavie and De Fockert, 2005 ), which posits that carrying out a more demanding primary task results in enhanced competition for the pool of limited executive control resources.…”
Section: Introductionsupporting
confidence: 64%
“…One hypothesized consequence of the aging process is increased susceptibility to distraction by irrelevant stimuli (Friedman et al, 1998 ; Andrés et al, 2006 ; Parmentier and Andrés, 2010 ). In the laboratory setting it has been shown that older individuals demonstrate enhanced early processing of irrelevant auditory stimuli during a visual oddball task (Tusch et al, 2016a ), and are more susceptible to distraction when performing working memory (Gazzaley et al, 2008 ; de Fockert et al, 2009 ), and reading-with-distraction tasks (Carlson et al, 1995 ; Li et al, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation